Calculations of Cross-Sections for Positron Scattering on Benzene - Małgorzata Franz; Anna Pastuszko; Jan Franz (Applied Sciences)
In this work, we present a theoretical study on positron scattering by benzene molecules over a broad energy range (1–1000 eV). The aim of this work is to provide missing data from partial cross-sections for specific processes. In particular, calculations of cross-sections for direct ionization and electronic excitation were carried out for benzene molecules in the gas phase. An estimate for the cross-section for positronium formation is obtained from a comparison with the total cross-section from experiments. Theoretical methodologies used in the study for partial ionization cross-section calculations are based on the binary-encounter Bethe model and take into account an extension of the Wannier theory. The total cross-section shows good agreement with experimental data.